2009
DOI: 10.1007/s10898-009-9444-9
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of finite exhausters

Abstract: Minkowski–Rådström–Hörmander spaces, Exhausters, Pairs of closed bounded convex sets, 46B20, 52A05, 54B20,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…After applying the developed procedure we usually get a family with many redundant sets. These sets can be discarded via various reduction techniques and methods presented in [38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…After applying the developed procedure we usually get a family with many redundant sets. These sets can be discarded via various reduction techniques and methods presented in [38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Neither the essentially primal graphical derivatives [16] nor dual coderivative objects [14] allow for well-defined dual characterisations. The exhauster approach is not without drawbacks: such constructions inherently lack uniqueness, and whilst some works are dedicated to finding minimal objects [17], it is shown that minimal exhausters do not exist in some cases [9]. The conjecture that we are studying in this paper is in a similar vein: we want to establish the uniqueness of a dual characterisation of a function by establishing a steady 2-cycle in the relevant dynamical system defined by the conversion operator.…”
Section: Introductionmentioning
confidence: 97%
“…Since the supremum of convex sets sup i∈I k∈I \{i} A k is the convex hull i∈I k∈I \{i} A k and the infimum inf i∈I A i is the intersection i∈I A i , the equivalence (c) ⇔ (e) follows immediately. The equivalence (b) ⇔ (c) follows from Theorem 5.2 in[15]. It should be mentioned, however, that in[15] the property (c) is called a shadowing property.The equivalence (e) ⇔ (f) is obvious.…”
mentioning
confidence: 93%
“…The equivalence (b) ⇔ (c) follows from Theorem 5.2 in[15]. It should be mentioned, however, that in[15] the property (c) is called a shadowing property.The equivalence (e) ⇔ (f) is obvious. By summand, we understand a summand with respect to Minkowski addition.…”
mentioning
confidence: 93%